Study Regarding Rural Farm Services that Contribute to the Increasing of Free Time - Cornelia Petroman; Simona Albu; S. Marin; Daniela Ienovan; I. Petroman; Diana Marin (Scientific Papers Animal Science and Biotechnologies, 2023)
The service structure that contribute to the increasing of free time in an agrotourist farm comprises a diverse range of activities, some of them with old t seniority, that have not undergone major changes, other recent or reinvented, for diversifying leisure but all with spectacular rates of development. One of the oldest activities is trade with products produced in agrotourist farm with an important role for producer of products, but also in report with the clients. Understanding the role of research and development services determines increasing the investments in scientific research in order to economic and social growth of agrotourist farms. Improving service in agrotourist farms has as consequence therefore redrafting time sequence which, potentially can be changed individually in free time, because the improvement level of  services offered to customers, determine the length of time allocated to developing a wide range of activities..